2008
DOI: 10.1002/rcm.3402
|View full text |Cite
|
Sign up to set email alerts
|

An exploratory comparative study of volatile compounds in exhaled breath and emitted by skin using selected ion flow tube mass spectrometry

Abstract: Selected ion flow tube mass spectrometry (SIFT-MS) has been used to carry out a pilot parallel study on five volunteers to determine changes occurring in several trace compounds present in exhaled breath and emitted from skin into a collection bag surrounding part of the arm, before and after ingesting 75 g of glucose in the fasting state. SIFT-MS enabled real-time quantification of ammonia, methanol, ethanol, propanol, formaldehyde, acetaldehyde, isoprene and acetone. Following glucose ingestion, blood glucos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

6
108
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 119 publications
(115 citation statements)
references
References 20 publications
6
108
1
Order By: Relevance
“…Mass spectral "fingerprints" obtained in-vivo from skin with desorption electrospray ionisation (DESI) [33], secondary electrospray ionisation (SESI) [34][35] and extractive electrospray ionisation (EESI) [36] are exciting and promising developments. Selected ion flow tube mass spectrometry (SIFT-MS) has provided real-time information for acetone emanating from skin [37] and proton transfer reaction mass spectrometry (PTR-MS) has been applied to monitoring of lipid peroxidation products and the fatty acid composition of skin [38]. All these methods enable fast, selective and sensitive analysis of the area of a participant's skin presented to the instrument.…”
Section: Introductionmentioning
confidence: 99%
“…Mass spectral "fingerprints" obtained in-vivo from skin with desorption electrospray ionisation (DESI) [33], secondary electrospray ionisation (SESI) [34][35] and extractive electrospray ionisation (EESI) [36] are exciting and promising developments. Selected ion flow tube mass spectrometry (SIFT-MS) has provided real-time information for acetone emanating from skin [37] and proton transfer reaction mass spectrometry (PTR-MS) has been applied to monitoring of lipid peroxidation products and the fatty acid composition of skin [38]. All these methods enable fast, selective and sensitive analysis of the area of a participant's skin presented to the instrument.…”
Section: Introductionmentioning
confidence: 99%
“…Detection of volatile compounds emitted from skin is even more demanding since their concentrations tend to be still lower than in breath, and the collection of skin gas is challenging. Despite this, a number of volatile compounds have been quantified in skin emission using SIFT-MS [20], gas chromatography coupled to flame-thermoionic and flame ionization detectors [21,22], laser-based photoacoustic detection and proton transfer reaction mass spectrometry (PTR-MS) [23]. The emission of hydrogen cyanide from skin has, however, to the best of our knowledge, not yet been documented.…”
Section: Introductionmentioning
confidence: 99%
“…10 It has also been reported that concentrations of acetone in both skin gas and exhaled air increased according to the length of fasting periods; 11 researchers also demonstrated that there is a good relationship between skin and exhaled air acetone concentration. 1,11 From these results, we can see that the skin gas acetone concentration reflects that of exhaled air.…”
Section: Introductionmentioning
confidence: 79%